2022
DOI: 10.3390/nu14102106
|View full text |Cite
|
Sign up to set email alerts
|

Sesamin Promotes Osteoporotic Fracture Healing by Activating Chondrogenesis and Angiogenesis Pathways

Abstract: Osteoporotic fracture has been regarded as one of the most common bone disorders in the aging society. The natural herb-derived small molecules were revealed as potential treatment approaches for osteoporotic fracture healing. Sesamin is a member of lignan family, which possesses estrogenic activity and plays a significant role in modulating bone homeostasis. Our previous study reported the promoting effect of sesamin on postmenopausal osteoporosis treatment. However, the role of sesamin in osteoporotic fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Lignans also alleviate neuroinflammation, reducing brain damage by preserving BDNF expression and modulating neurotransmitter levels. Surprisingly, some of the lignans showed impressive efficacy on postmenopausal symptoms compared to extrinsic hormones such as parathyroid hormone or estrogen [ 88 , 103 ]. It was confirmed that TNF-α expression was more strongly suppressed when treated with lignans derived from Sambucus Willaimsii compared to parathyroid hormone treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignans also alleviate neuroinflammation, reducing brain damage by preserving BDNF expression and modulating neurotransmitter levels. Surprisingly, some of the lignans showed impressive efficacy on postmenopausal symptoms compared to extrinsic hormones such as parathyroid hormone or estrogen [ 88 , 103 ]. It was confirmed that TNF-α expression was more strongly suppressed when treated with lignans derived from Sambucus Willaimsii compared to parathyroid hormone treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Zhengmeng Yang et al also discovered the anti-osteoclastogenesis effect of Ses to be mediated by NF-κB pathway inhibition, which reduces the expression of CTSK and tartaric-acid phosphatase (TRAP) in osteoclasts [ 102 ]. Moreover, healing of osteoporotic fractures in C57BL/6 mice following OVX surgery was improved by oral administration of Ses [ 103 ]. Ses upregulated the expression of VEGF, an angiogenesis marker, along with bone morphogenetic protein 2 (BMP2) and SOX9, both chondrogenesis markers.…”
Section: Anti-menopausal Effects Of Lignansmentioning
confidence: 99%
“…Quercetin is identified as an antiosteoporotic flavonoid, which promotes osteogenesis, antioxidant expression, angiogenesis, osteoclast, and adipocyte apoptosis, while inhibiting RANKL-mediated osteoclastogenesis, osteoblast apoptosis, oxidative stress, and inflammatory response [35]. Sesamin, a member of the lignan family, has estrogenic activity and plays an important role in healing osteoporotic fracture by activating angiogenesis and chondrogenesis [36]. Moreover, existing study reveals that sesamin could promote osteogenesis by upregulating the Wnt/ β-catenin pathway and inhibit osteoclastogenesis by downregulating the NF-κB pathway, suggesting that it could be a therapeutic medication for osteoporosis treatment [37].…”
Section: Discussionmentioning
confidence: 99%
“…The peroxidase-streptavidin substrate kit (DAKO, Carpinteria, CA, USA) was applied for substrate reaction. Additionally, the images were taken by a semi-automatic digitizing image analysis system (OsteoMetrics, Atlanta, GA, USA) [ 35 ].…”
Section: Methodsmentioning
confidence: 99%